The contribution of policy, law, management, research, and advocacy failings to the recent extinctions of three Australian vertebrate species. Issue 1 (9th November 2016) - Woinarski, John C.Z.; Garnett, Stephen T.; Legge, Sarah M.; Lindenmayer, David B.
Abstract: Extinctions typically have ecological drivers, such as habitat loss. However, extinction events are also influenced by policy and management settings that may be antithetical to biodiversity conservation, inadequate to prevent extinction, insufficiently resourced, or poorly implemented. Three endemic Australian vertebrate species—the Christmas Island pipistrelle ( Pipistrellus murrayi ), Bramble Cay melomys ( Melomys rubicola ), and Christmas Island forest skink ( Emoia nativitatis )—became extinct from 2009 to 2014. All 3 extinctions were predictable and probably preventable. We sought to identify the policy, management, research, and other shortcomings that contributed to their extinctions or failed to prevent them. These included a lack within national environmental legislation and policy of explicit commitment to the prevention of avoidable extinctions, lack of explicit accountability, inadequate resources for conservation (particularly for species not considered charismatic or not of high taxonomic distinctiveness), inadequate biosecurity, a slow and inadequate process for listing species as threatened, recovery planning that failed to consider the need for emergency response, inability of researchers to identify major threatening factors, lack of public engagement and involvement in conservation decisions, and limited advocacy. From these 3 cases, we recommend: environmental policy explicitly seeks to prevent extinction of any species and provides a clear chain of accountability and an explicit requirement for public inquiry following any extinction; implementation of a timely and comprehensive process for listing species as threatened and for recovery planning; reservation alone not be assumed sufficient to maintain species; enhancement of biosecurity measures; allocation of sufficient resources to undertake actions necessary to prevent extinction; monitoring be considered a pivotal component of the conservation response; research provides timely identification of factors responsible for decline and of the risk of extinction; effective dissemination of research results; advocacy by an informed public for the recovery of threatened species; and public involvement in governance of the recovery process. These recommendations should be applicable broadly to reduce the likelihood and incidence of extinctions.